2018
DOI: 10.1108/ijoes-05-2017-0080
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of financial reporting fraud intention among accounting practitioners in the banking sector

Abstract: Purpose -This study aims to examine the influence of attitude, subjective norm and ethical judgement on unethical financial reporting intention among Malaysian accounting practitioners in the banking industry.Design/methodology/approach -For achieving the objective, a questionnaire survey was used. With the inclusion of 121 samples of participants in the financial reporting process, data analysis was conducted using partial least square structural equation modelling (PLS-SEM).Findings -The results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 58 publications
1
30
1
5
Order By: Relevance
“…model provides a more comprehensive approach of investigating fraud determinants, the five factors are by no means exhaustive in explaining why individuals engage in fraud. Empirically, some existing studies have also found the effect of ethical values of an individual be particularly relevant in the fraud determinants discourse (Awang and Ismail, 2017;Mintz, 2006;Said et al, 2017). This study, therefore, includes ethical values as a controlling variable.…”
Section: Egomentioning
confidence: 97%
See 1 more Smart Citation
“…model provides a more comprehensive approach of investigating fraud determinants, the five factors are by no means exhaustive in explaining why individuals engage in fraud. Empirically, some existing studies have also found the effect of ethical values of an individual be particularly relevant in the fraud determinants discourse (Awang and Ismail, 2017;Mintz, 2006;Said et al, 2017). This study, therefore, includes ethical values as a controlling variable.…”
Section: Egomentioning
confidence: 97%
“…Findings from these studies suggest that people engage in fraudulent acts because they do not have ethical values or they do not respect the ethical codes at their workplaces. However, individuals with strong ethical beliefs hardly commit fraud (Awang and Ismail, 2017;Mintz, 2006;Said et al, 2017). Hence, the study hypothesizes that:…”
Section: Ethical Values and Asset Misappropriationmentioning
confidence: 99%
“…Meanwhile, referring to some of the previous research, there were not many kinds of research related to whistleblowing intentions in the banking industry. Based on research by Awang & Ismail (2018), employees who play a role in the financial reporting process in banks in Malaysia showed a high intention to commit fraud.…”
Section: Theory Of Planned Behavior and Whistleblowing Intentionmentioning
confidence: 99%
“…Meanwhile, according to Ajzen (1991) to explain the actual behavior of individuals, what can be done is to identify the intention or tendency of individuals to display such behavior. Awang & Ismail (2018) also said that to observe actual behavior is a highly tough thing to be done. Therefore, behavior can be identified by observing the potential of its occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Sebuah hasil penelitian menyatakan bahwa sikap terhadap perilaku berpengaruh signifikan terhadap kecenderungan kecurangan laporan keuangan. Apabila sikap individu cenderung positif terhadap kecurangan laporan keuangan dan ia merasa bahwa perilaku tersebut adalah benar walaupun melanggar prinsip akuntansi dan norma subjektif, kemungkinan besar perilakunya akan mengarah pada pelanggaran tersebut (Awang, Abdul Rahman, & Ismail, 2019;Awang & Ismail, 2018). Hal semacam ini dapat terjadi dikarenakan sikap individu menentukan persepsi dan niatan individu mengenai suatu hal dan cara ia berperilaku (Mahyarni, 2013).…”
Section: Sikap (Attitude) Individuunclassified